Contemporary Aspect Of Grant And Inheritance To Children (Study Philosophy Of Islamic Law) - Nurfaizah, Nurfaizah; Sabri Samin; Ahmad Musyahid; Misbahuddin Amin (Cita konsultindo, 2023)
Abstract: Inheritance is the inheritance of an heir who has passed away to his heirs with sababiyah and nasabiyah relationships. Whereas a grant is a gift to someone for the assets they own, either to children or other relatives during their lifetime. The purpose of this research is to find out the theoretical review of inheritance and grants to children in the perspective of Islamic law, with this type of qualitative research and using a normative method. As a result of research that inheritance to children is an absolute right that is obtained by a child as a legal heir, while grants to children are gifts that provide the initial inheritance from their parents. So that it is categorized as inherited property and can be withdrawn. Keywords: Inheritance; Grant; Children; Islamic Law.